The Reciprocal Learning Based on Google Sites to Improve Learning Achievement and Student Activity in Earth and Solar System Material for Grade VII SMP - Puji Siswoyo, Wuryanto (Science and Education Journal (SICEDU), 2024)
This research aims to describe the activity of students during the implementation of reciprocal learning based on Google Sites and describe the completeness of student learning. This research was conducted using a classroom action research method consisting of two cycles. The research was carried out in class VII at SMPN 3 Satu Atap Borobudur. Data collection techniques use observation, interviews, questionnaires and tests. Descriptive analysis of learning achievement and activity of students using the SPSS version 26 application. The prerequisites carried out are the normality test, homogeneity test and correlation test. Descriptive analysis uses the paired sample t test for weakly correlated data and uses the Manova test if the data is strongly correlated, as well as the Wilcoxon test for non-normally distributed data. Student activity increased from cycle I in the quite good category (66, 07%) became good (75.00%) in cycle II or there was an increase of 8.93% and student learning completeness increased so that they reached classical completeness from 71.43% in cycle I to 76.19% in cycle II or there was an increase amounted to 4.76%.